Rosuvastatin Can Block Pro‐Inflammatory Actions of Transgenic Human C‐Reactive Protein Without Reducing its Circulating Levels. Issue 2 (April 2014) - Šilhavý, Jan; Zídek, Václav; Landa, Vladimír; Šimáková, Miroslava; Mlejnek, Petr; Škop, Vojtěch; Oliyarnyk, Olena; Kazdová, Ludmila; Mancini, Massimiliano; Saar, Kathrin; Schulz, Herbert; Hübner, Norbert; et al.
Summary Aims Statins have antiinflammatory effects and are known to decrease risk of cardiovascular events and to reduce serum levels of C‐reactive protein (CRP), a widely studied biomarker and potential mediator of inflammation and heart disease. However, it is unclear whether statins can block pro‐inflammatory effects of human CRP independent of their ability to reduce serum levels of human CRP. Here, we investigated whether rosuvastatin could block pro‐inflammatory effects of human CRP without reducing circulating levels of human CRP. Methods and Results We studied the antiinflammatory effects of rosuvastatin in spontaneously hypertensive rats (SHR) transgenically expressing human CRP (CRP‐transgenic SHR) and in nontransgenic SHR lacking human CRP (nontransgenic SHR). The CRP‐transgenic SHR is characterized by increased serum levels of human CRP and inflammation. In the CRP‐transgenic strain, we found that rosuvastatin treatment decreased circulating levels of inflammatory response markers IL6 and TNFα without decreasing circulating levels of human CRP. In contrast, in the nontransgenic strain lacking human CRP, rosuvastatin treatment had little or no effect on IL6 and TNFα levels. Rosuvastatin also reduced cardiac inflammation and oxidative tissue damage, reduced epididymal fat mass, and improved adipose tissue lipolysis much more in the CRP‐transgenic strain than in the nontransgenic strain. Conclusion Rosuvastatin can protect against pro‐inflammatory effects of human CRP in a manner that is not dependent on achieving a reduction in circulating levels of human CRP.